Peran Guru dalam Stimulasi Perkembangan Bahasa Anak Usia Dini - Suci Rahmadani Lubis; Syamsiah Depalina (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Language development is one of the main pillars in early childhood growth. Strong language skills are not just about being able to speak, but also include the ability to listen, understand, and use language to think and interact. This ability becomes an important foundation for children's future success, both in formal education and social life. In the early childhood stage, the role of teachers in kindergartens (TK) is very crucial. Teachers are the child's first social environment outside the home, and the interactions they have every day will greatly influence the child's language development. This research will thoroughly explore the various strategic roles played by teachers in stimulating children's language development, and how these roles can be effectively applied in the classroom environment.